Application of thoracic endovascular aortic repair (TEVAR) in treating dwarfism with Stanford B aortic dissection: A case report. Issue 17 (April 2018) - Qiu, Jian; Cai, Wenwu; Shu, Chang; Li, Ming; Xiong, Qinggen; Li, Quanming; Li, Xin
Abstract: Rationale: To apply thoracic endovascular aortic repair (TEVAR) to treat dwarfism complicated with Stanford B aortic dissection. Patient concerns: In this report, we presented a 63-year-old male patient of dwarfism complicated with Stanford B aortic dissection successfully treated with TEVAR. Diagnoses: He was diagnosed with dwarfism complicated with Stanford B aortic dissection. Interventions: After conservative treatment, the male patient underwent TEVAR at 1 week after hospitalization. After operation, he presented with numbness and weakness of his bilateral lower extremities, and these symptoms were significantly mitigated after effective treatment. At 1- and 3-week after TEVAR, the aorta status was maintained stable and restored. Outcomes: The patient obtained favorable clinical prognosis and was smoothly discharged. During subsequent follow-up, he remained physically stable. Lessons: TEVAR is probably an option for treating dwarfism complicated with Stanford B aortic dissection, which remains to be validated by subsequent studies with larger sample size.